METHOD FOR MANUFACTURING SiC
Patent Information
- Application Number
- JP2023148502
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
Smart Images

Figure 2025041304000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing SiC. [Background technology]
[0002] SiC has excellent properties such as high hardness, heat resistance, wear resistance, acid resistance, and corrosion resistance. Therefore, it is expected to be used for metal coating, etc. For example, forming SiC on a metal can improve the durability of the electrode and enable the use of inexpensive base metals.
[0003] When forming SiC on a metal substrate, it is necessary to grow it at a low temperature to suppress melting of the metal and formation of metal silicide. A method capable of forming a film at a low temperature is disclosed in Non-Patent Document 1. Non-Patent Document 1 describes the formation of a SiC film on a Cu substrate by thermal CVD at 700°C using vinylsilane as a raw material. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Doi et al., Low-temperature formation of SiC thin films by thermal CVD using vinylsilane, Proceedings of the 78th Autumn Meeting of the Japan Society of Applied Physics, 7a-A201-5, August 25, 2017 Summary of the Invention [Problem to be solved by the invention]
[0005] However, Fe, Co, and Ni easily form silicides, making it difficult to form SiC on metal layers that contain these elements as their main components.
[0006] The present invention has been made in view of the above background, and aims to provide a method for producing SiC, which can form SiC on a metal layer whose main component is any of Fe, Co, and Ni. [Means for solving the problem]
[0007] One aspect of the present invention is A method for producing SiC by forming SiC on a substrate by a thermal CVD method using vinylsilane as a raw material, the substrate has a metal layer as a top layer, the metal layer being a metal containing any one of Fe, Co, and Ni as a main component; The method for producing SiC involves forming SiC by setting the growth temperature at 1000° C. or less.
[0008] Another aspect of the present invention is The fiber material comprises carbon fibers having a diameter of 5 nm to 100 nm and a length of 100 nm to 10 μm, and SiC coating the carbon fibers. Effect of the Invention
[0009] In the above embodiment, the growth temperature is controlled according to the thickness of the metal layer. This allows SiC to be formed even on a metal layer whose main components are Fe, Co, and Ni. Also, carbon fibers coated with SiC can be formed on the metal layer. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a diagram showing a schematic configuration of a thermal CVD apparatus used in the method for producing SiC in the embodiment. [Diagram 2] SEM images of the substrate surface before and after SiC growth. [Diagram 3] Graph showing the results of XPS measurements, showing Cu2p for SiC on a Cu substrate, Fe2p for SiC on a SUS substrate, and Ti2p for SiC on a Ti substrate. [Figure 4] 1 is a graph showing the results of XPS measurements, illustrating Si2p for SiC of various substrates. [Diagram 5] 1 is a graph showing the results of XPS measurements, showing C1s for SiC of various substrates. [Figure 6] Graph showing the results of electrochemical measurements for a SUS substrate. [Figure 7] Graph showing the results of electrochemical measurements when an n-type SiC-coated SUS substrate is used. [Figure 8] 1 is a graph showing the relationship between the current density of the reduction peak current and the number of cycles. [Figure 9] SEM images of the substrate surface before and after SiC growth. [Figure 10] Cross-sectional SEM image after SiC growth. [Figure 11] Graph showing the results of X-ray diffraction measurement of SiC when the metal layer is Fe. [Figure 12] Graph showing the results of X-ray diffraction measurement of SiC when the metal layer is Co. [Figure 13] Graph showing the results of Raman spectroscopy measurement when the growth temperature was 750° C. [Figure 14] Graph showing the results of Raman spectroscopy measurement when the growth temperature was 950° C. [Figure 15] SEM image of the substrate surface after SiC formation. [Figure 16] 1 is a graph showing the results of Raman spectroscopy. [Figure 17] 1 is a graph showing the results of analysis by XPS, the graph showing Si2p. [Figure 18] 1 is a graph showing the results of analysis by XPS, the graph showing C1s. [Figure 19] 1 is a graph showing the results of analysis by XPS, the graph showing Fe2p. [Figure 20] 1 is a graph showing the results of FT-IR analysis of the formed Al-doped SiC. [Figure 21] Graph showing the results of X-ray diffraction measurement of Al-doped SiC. [Figure 22] 1 is a graph showing the results of XPS measurements, illustrating Si2p. [Diagram 23] 1 is a graph showing the results of XPS measurement, the graph showing C1s. [Figure 24] 1 is a graph showing the results of XPS measurement, showing O1s. [Diagram 25] 1 is a graph showing the results of XPS measurement, the graph showing Al2p. [Figure 26] Graph showing the composition ratio of Al-doped SiC. [Figure 27] Graph showing the relationship between resistivity and Al composition of Al-doped SiC. [Figure 28] Graph showing the results of measuring the Hall effect for Al-doped SiC. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The method for producing SiC involves forming SiC on a substrate by thermal CVD using vinylsilane as a raw material, the substrate having as its top layer a metal layer whose main component is either Fe, Co or Ni, and the SiC is formed by setting the growth temperature to 1000°C or lower.
[0012] Here, the thickness of the metal layer may be 200 nm or less.
[0013] By setting the thickness of the metal layer to 200 nm or less and the growth temperature to 800° C. or less, SiC can be formed in a granular shape.
[0014] Moreover, by setting the thickness of the metal layer to 200 nm or less and the growth temperature to be higher than 800° C. and equal to or lower than 900° C., it is possible to form SiC in a pillar shape.
[0015] Moreover, by making the thickness of the metal layer greater than 200 nm and setting the growth temperature to 900° C. or less, SiC can be formed in a granular shape.
[0016] In addition, by setting the thickness of the metal layer to 200 nm or less and the growth temperature to be higher than 900°C and lower than 1000°C, the silicide can be grown in a hemispherical shape, and then SiC can be formed on the surface of the silicide, thereby forming hemispherical SiC.
[0017] In addition, by making the metal layer thicker than 200 nm and setting the growth temperature to above 900°C to form carbon fibers on the metal layer, and then setting the growth temperature to 900°C or lower, it is possible to form SiC coating the carbon fibers.
[0018] Al-doped p-type SiC may be formed by mixing vinylsilane with trimethylaluminum and supplying the mixture. The Al-doped p-type SiC may have a ratio of Al to SiC of 1 at % or less.
[0019] The flow rate of vinylsilane may be 1 to 50 sccm. The growth pressure may be 100 Pa or less.
[0020] The fiber material includes carbon fibers having a diameter of 5 nm to 100 nm and a length of 100 nm to 10 μm, and SiC coating the carbon nanofibers.
[0021] (Embodiment) 1. Overview of the embodiment In the method for producing SiC in the embodiment, SiC is formed by thermal CVD on a metal layer made of a metal containing Fe, Co, and Ni as main components.
[0022] Thermal CVD is a method of forming a film on a substrate by supplying source gas to the substrate and thermally decomposing the source gas on the substrate. By using thermal CVD, the growth temperature of SiC can be reduced, so that SiC can be formed on a metal layer. Thermal CVD may be a cold wall method that heats only the substrate, or a hot wall method that heats the entire reaction chamber.
[0023] 2. Thermal CVD Equipment Configuration An example of a thermal CVD apparatus used in the SiC manufacturing method of the embodiment is shown in Fig. 1. The thermal CVD apparatus shown in Fig. 1 is a hot-wall type thermal CVD apparatus, and includes a reaction chamber 10, a stage 11, a heater 12, a supply pipe 13, and an exhaust pipe 14.
[0024] The reaction chamber 10 is a hollow container, such as a quartz tube, in which film formation is carried out by thermal CVD.
[0025] The stage 11 is disposed within the reaction chamber 10. The stage 11 is a platform on which the substrate S is placed.
[0026] The heater 12 is disposed near the outside of the reaction chamber 10. The heater 12 is a heating device that heats the entire reaction chamber 10.
[0027] The supply pipe 13 is a pipe that supplies a source gas or a mixed gas of a source gas and a carrier gas into the reaction chamber 10. The source gas is vinylsilane as described below. The exhaust pipe 14 is a pipe that exhausts the gas inside the reaction chamber 10. The above is an example of a thermal CVD apparatus. The thermal CVD apparatus may be of a cold wall type.
[0028] 3. Manufacturing method of SiC Next, a method for producing SiC in the embodiment will be described.
[0029] First, a substrate S is prepared. The substrate S has a metal layer as the uppermost layer. The substrate S may be a metal substrate, or may be an insulating substrate or a substrate in which a metal layer is formed on a semiconductor substrate. For example, the substrate S may have a structure in which the entire substrate is a metal layer, a structure in which a metal layer is formed on a Si substrate via an insulating film such as SiO2, or a structure in which a metal layer is formed on an insulating substrate such as SiO2.
[0030] The metal layer is made of a metal containing Fe, Co, or Ni as a main component, for example, Fe, Co, Ni, or an alloy containing Fe as a main component, such as SUS.
[0031] The ferromagnetic materials Fe, Co, and Ni easily react with Si to form silicides. For this reason, it was previously difficult to form SiC on a metal layer mainly composed of these elements. However, through intensive research by the inventors, it was discovered that it is possible to form SiC on a metal layer mainly composed of these elements by using thermal CVD as the film formation method, vinylsilane as the raw material gas, and setting the growth temperature within a predetermined range according to the thickness of the metal layer. Details will be described later.
[0032] Next, the surface of the substrate S is chemically cleaned. For example, the surface of the substrate S is cleaned using an aqueous solution of ammonia and hydrogen peroxide, and further cleaned using hydrofluoric acid.
[0033] Next, the substrate S is carried into the reaction chamber 10 of the thermal CVD apparatus, and the substrate S is placed on the stage 11. Then, the reaction chamber 10 is sealed.
[0034] Next, the reaction chamber 10 is evacuated, the substrate S is heated by the heater 12, and hydrogen is supplied into the reaction chamber 10. This thermally cleans the surface of the substrate S. Hydrogen is supplied in a state mixed with an inert gas such as nitrogen or Ar.
[0035] The chemical cleaning or thermal cleaning of the substrate S may be performed as necessary, and only one of them may be performed, or neither may be performed.
[0036] Next, the supply of hydrogen into the reaction chamber 10 is stopped, and an inert gas is supplied to purge the reaction chamber 10. Then, the reaction chamber 10 is heated to a growth temperature by the heater 12, and a source gas is supplied into the reaction chamber 10 to grow SiC on the surface of the substrate S.
[0037] Vinylsilane (CH2=CH-SiH3) is used as the source gas. Vinylsilane contains Si-C bonds and Si-H bonds, but since the Si-H bonds decompose first, the Si-H bonds are less likely to remain in the film, and high-quality SiC can be formed. Furthermore, vinylsilane serves as both a Si source and a C source, and there is no need to control the composition, making it easy to control the source gas. The flow rate of vinylsilane is preferably 1 to 50 sccm. Within this range, high-quality SiC can be formed. More preferably, it is 1 to 20 sccm.
[0038] When supplying the raw material gas, it may be mixed with a carrier gas before supplying. An inert gas can be used as the carrier gas. For example, nitrogen or a rare gas such as Ar. In this case, the volume ratio of the raw material gas to the mixed gas is preferably 1 to 3%. This makes it easier to control the raw material gas.
[0039] A dopant gas may be mixed into the raw material gas. The conductivity type of SiC can be controlled by introducing impurities into SiC. P can be used as the n-type impurity. When the n-type impurity is P, phosphorus trifluoride, diphenylphosphine, etc. can be used as the n-type dopant gas.
[0040] Moreover, Al or the like can be used as the p-type impurity. When Al is used as the p-type impurity, trimethylaluminum (TMA) or the like can be used as the p-type dopant gas. It is preferable to adjust the flow rate of TMA so that Al is 2 at% or less with respect to SiC. If it is 2 at% or less, it is possible to prevent Al and C from reacting to form Al4C3, and it is possible to form low-resistance p-type SiC. It is more preferable that it is 1 at% or less. The hole concentration of Al-doped p-type SiC is, for example, 1×10 16 ~1×10 18 cm -3 It can be said that:
[0041] The growth temperature is 1000°C or less. By setting the growth temperature to 1000°C or less, the reaction between the metal of the metal layer and Si and the formation of silicide is suppressed, and a high-quality SiC film can be formed. There is no particular lower limit for the growth temperature. It is sufficient if the temperature is within a range in which SiC can be formed.
[0042] It is preferable to reduce the growth pressure, since this allows the SiC film to be formed with higher quality. For example, a pressure of 100 Pa or less is preferable.
[0043] SiC can be formed at a growth temperature in the range of up to 1000° C. The shape of the SiC can be controlled to various shapes by controlling the growth temperature according to the thickness of the metal layer.
[0044] First, we will explain the case where the thickness of the metal layer is 200 nm or less. In this case, if the growth temperature is low enough, the SiC will be in the form of a film, and as the growth temperature increases, the shape will change to granular, pillar-like, and hemispherical. Also, the higher the growth temperature, the better the crystallinity will be.
[0045] When the growth temperature is 800°C or lower, SiC grows in a granular or film-like shape. In general, the lower the growth temperature, the easier it is to grow in a film-like shape. Therefore, it is possible to control the granular or film-like shape by changing the growth temperature depending on the material of the metal layer. When the growth is granular, the grain diameter is about 10 to 100 nm.
[0046] When the growth temperature is higher than 800°C and equal to or lower than 900°C, SiC grows in a pillar shape. Here, pillar shape means a thin and long columnar or linear shape extending in the direction perpendicular to the substrate. The diameter of the pillar can be about 10 to 200 nm, and the height of the pillar can be about 100 nm to 10 μm.
[0047] When the growth temperature is higher than 900℃ and lower than 1000℃, SiC grows in a hemispherical shape. This is a structure in which the surface of a hemispherical silicide is coated with SiC. The reason for the formation of such a structure is thought to be as follows.
[0048] When the growth temperature is high, above 900°C and below 1000°C, the metal in the metal layer reacts with the Si in the vinylsilane to form silicides on the metal layer. The metals, mainly Fe, Co, and Ni, make it easier for the Si-C bonds in the vinylsilane to break down, which is thought to make it easier for silicides to form. The silicides that form are rounded into a hemispherical shape due to the balance with the surface energy. Here, since the metal layer is thin, at 200 nm or less, after a sufficient amount of time has passed, the metal reacts completely and the metal layer disappears, and the formation of silicides stops. Then, the decomposition of the Si-C bonds by the metal layer stops, and SiC is formed to cover the surface of the hemispherical silicide. As a result, hemispherical SiC is formed.
[0049] The diameter of the hemispherical SiC may be, for example, 0.5 to 5 μm, and the thickness of the SiC coating the silicide may be, for example, 10 to 100 nm.
[0050] As described above, when the metal layer is 200 nm or less, various shapes of SiC can be formed by changing the growth temperature. In particular, if the SiC is shaped like a grain, pillar, or hemisphere, the surface area of the SiC can be increased.
[0051] Next, a case where the thickness of the metal layer is made thicker than 200 nm will be described. When the metal layer is thicker than 200 nm, SiC can be grown in a granular shape by setting the growth temperature to 900° C. or less. The diameter of the grains is, for example, 10 to 100 nm.
[0052] If the growth temperature is higher than 900°C and lower than 1000°C, carbon fibers can be grown on the metal layer. Carbon fibers are long, fibrous carbon. If the growth temperature is lowered to 900°C or lower after the carbon fibers are formed, the surface of the carbon fibers can be coated with SiC. Coating the carbon fibers with SiC can improve the hardness, thermal conductivity, chemical stability, etc. of the carbon fibers.
[0053] The carbon fibers have a diameter of, for example, 5 to 100 nm, a length of, for example, 100 nm to 10 μm, and a thickness of, for example, 5 to 10 nm of SiC coating the carbon fibers.
[0054] As described above, in the method for producing SiC in the embodiment, the thermal CVD method is used as the film formation method, and the raw material gas is vinylsilane, so that SiC can be formed on a metal layer mainly composed of Fe, Co, and Ni. In particular, the shape of SiC can be controlled by controlling the thickness and growth temperature of the metal layer. In addition, a protective layer such as Ti may be further formed on the formed SiC. The protective layer can be formed by sputtering, deposition, or the like.
[0055] Furthermore, according to the method for producing SiC in the embodiment, a fiber material in which carbon fibers are coated with SiC can be formed.
[0056] 4. Explanation of various experimental results Next, various experimental results relating to the embodiment will be described.
[0057] Experiment 1 Substrates of various materials were prepared, and SiC was formed on the substrates by thermal CVD with vinylsilane as the source gas and a growth temperature of 650°C. The growth pressure was 15 Pa and the growth time was 1 hour. The substrates prepared were Si, Cu, SUS, and Ti. Figures 2(a) and (b) are SEM images of the substrate surfaces, (a) before SiC growth and (b) after SiC growth. As shown in Figures 2(a) and (b), it was confirmed that SiC grew in the form of a flat film on all substrates. Since the SUS substrate is a metal whose main component is Fe, it is thought that it easily reacts with Si to form silicides, but it was found that if the growth temperature is sufficiently low, the generation of silicides can be suppressed and SiC can be grown.
[0058] Next, elemental analysis was performed by XPS on the SiC grown on various substrates. Figures 3 to 5 are graphs showing the results of XPS measurement, with Figure 3 showing Cu2p for SiC on a Cu substrate, Fe2p for SiC on a SUS substrate, and Ti2p for SiC on a Ti substrate, Figure 4 showing Si2p for SiC on various substrates, and Figure 5 showing C1s for SiC on various substrates.
[0059] As shown in Figure 3, an Fe2p peak was observed on the SUS substrate, but not on the SiC on the SUS substrate. Also, as shown in Figure 4, an Si-C peak of Si2p was observed on the SiC on the SUS substrate, and as shown in Figure 5, a C-Si peak of C1s was observed. As a result, it was confirmed that the film formed on the SUS substrate was indeed SiC. Similarly, it was also confirmed that SiC was formed on the Si substrate, Cu substrate, and Ti substrate.
[0060] Experiment 2 P-doped n-type SiC was formed on a SUS substrate. The growth conditions were the same as in Experiment 1. Then, this n-type SiC-coated SUS substrate was used as the working electrode, and electrochemical measurements were performed by cyclic voltammetry. Pt was used as the counter electrode, Ag|AgCl was used as the reference electrode, and a 0.5 mol / L aqueous sodium sulfate solution was used. The number of cycles was 300. For comparison, electrochemical measurements were also performed on the SUS substrate in the same way.
[0061] Figures 6 and 7 are graphs showing the results of electrochemical measurements, where Figure 6 shows the results for a SUS substrate and Figure 7 shows the results for an n-type SiC-coated SUS substrate, and Figure 8 shows the relationship between the current density of the reduction peak current and the number of cycles.
[0062] As shown in Figure 6, when a SUS substrate was used as the working electrode, it was found that the oxidation peak current and reduction peak current fluctuated significantly with an increase in the number of cycles. In addition, when the SUS substrate was visually inspected after 300 cycles, it was confirmed that it had corroded and become thinner. In addition, as shown in Figure 8, it was found that the current density of the reduction peak current also increased with an increase in the number of cycles.
[0063] On the other hand, when a SiC-coated SUS substrate was used, the oxidation peak current and reduction peak current hardly changed even with an increase in the number of cycles, as shown in Figure 7. Furthermore, no corrosion was observed when the SiC-coated SUS substrate was visually inspected. Furthermore, as shown in Figure 8, the current density of the reduction peak current hardly increased even with an increase in the number of cycles.
[0064] The results of Figures 6 to 8 show that when a SUS substrate is used as an electrode for electrolysis, the deterioration of the electrode can be significantly suppressed by coating the SUS substrate with SiC.
[0065] Experiment 3 Substrates of various materials were prepared, and SiC was formed on the substrates by thermal CVD. All conditions were the same as in Experiment 1, except for the growth temperature. The growth temperature was 750°C. The substrates used were Si substrates with a metal layer provided on top of SiO2, and the metal layers were Fe, Co, Ni, Au, and Ti. The Si substrates used had a (100) surface as their main surface. The SiO2 was 500nm thick, and the metal layer was 100nm thick.
[0066] Figure 9 shows SEM images of the substrate surface before and after SiC growth. As shown in Figure 9, when the metal layer was Fe, Co, or Ni, granular SiC was formed on the metal layer. Also, when the metal layer was Au or Ti, film-like SiC was formed on the metal layer. It is believed that Fe, Co, and Ni form silicides more easily than Au and Ti, which is why the shapes of the SiC are different.
[0067] Next, the growth temperature was changed to 850°C and SiC was formed under the same conditions. Figure 10 is a cross-sectional SEM image of SiC after growth. As shown in Figure 10, when the metal layer was Fe or Co, it was found that the shape of the SiC was pillar-like. It was therefore possible to form SiC with a large surface area. On the other hand, when the metal layer was Ti, it was found that the SiC was granular. In this way, it was found that as the growth temperature was increased, the SiC changed from film-like to granular to pillar-like.
[0068] Next, SiC was grown under the same conditions with growth temperatures of 750°C and 950°C. X-ray diffraction measurements were then performed on the formed SiC. Figure 11 is a graph showing the measurement results when the metal layer was Fe, and Figure 12 is a graph showing the measurement results when the metal layer was Co. As shown in Figures 11 and 12, a silicide peak was observed when the growth temperature was 750°C. On the other hand, no silicide peak was observed when the growth temperature was 950°C. Also, the SiC peak was more clearly observed when the growth temperature was higher. As a result, it was found that the crystallinity of SiC was higher when the growth temperature was higher.
[0069] Next, SiC was grown under the same conditions at growth temperatures of 750°C and 950°C, and Raman spectroscopy was performed. Figures 13 and 14 are graphs showing the results of Raman spectroscopy, with Figure 13 being for a growth temperature of 750°C and Figure 14 being for a growth temperature of 950°C. As shown in Figure 13, at a growth temperature of 750°C, peaks due to C were observed for Fe, Co, and Ni. This indicates that ferromagnetic materials tend to break the C-Si bond of vinylsilane to form silicides. Also, as shown in Figure 14, at a growth temperature of 950°C, no peaks due to C were observed even for Fe, Co, and Ni. This is thought to be because Fe, Co, and Ni react with Si to the point where the formation of silicides stops, and SiC grows on the surface.
[0070] Experiment 4 Substrates of various materials were prepared, and SiC was formed on the substrates by thermal CVD using vinylsilane as the source gas and three growth temperatures of 650°C, 750°C, and 950°C. The growth pressure was 15 Pa, and the growth time was 1 hour. Two types of substrates were prepared: an Fe substrate and a Si substrate with a metal layer made of Fe formed on SiO2. The thickness of the Fe substrate was 800μm, and the thickness of the metal layer was 100nm.
[0071] Figure 15 shows an SEM image of the substrate surface after SiC formation. As shown in Figure 15, when the growth temperatures were 650°C and 750°C, granular SiC was formed on both the Fe substrate and the Fe thin film. The grain diameter was 10 to 100 nm.
[0072] It was also found that hemispherical SiC was formed on the Fe thin film at a growth temperature of 950° C. The diameter of the SiC was 0.5 to 5 μm.
[0073] Moreover, at a growth temperature of 950° C., no SiC was formed on the Fe substrate, but carbon fibers were formed. The diameter of the carbon fibers was 5 to 100 nm, and the length was 100 nm to 10 μm.
[0074] Figure 16 is a graph showing the results of Raman spectroscopy measurements at growth temperatures of 650°C and 950°C. At a growth temperature of 650°C, C-derived bonds were observed in both the Fe substrate and the Fe thin film. At a growth temperature of 950°C, C-derived bonds were observed in the Fe substrate, but not in the Fe thin film.
[0075] Figures 17 to 19 are graphs showing the results of analysis by XPS, with Figure 17 being Si2p, Figure 18 being C1s, and Figure 19 being Fe2p. Figure 19 shows that Fe was not observed in the Fe thin film after the growth of SiC. It is believed that the Fe thin film disappeared due to the generation of silicide. Figures 17 and 18 also show Si-C bonds. It is therefore believed that the silicide is coated with SiC. Figures 17 and 18 also show that C-C bonds are dominant in the Fe substrate, and that the fibers on the Fe substrate are carbon fibers.
[0076] Experiment 5 Al-doped SiC was formed on a Si substrate by thermal CVD. Vinylsilane and TMA were used as source gases. In addition, several samples with different TMA flow rates were prepared by changing the needle valve opening length.
[0077] Figure 20 is a graph showing the results of FT-IR analysis of the formed Al-doped SiC. From Figure 20, a Si-CH3 peak was observed when the needle valve opening length was 0.50 mm. As a result, it was found that when the TMA flow rate was high, TMA did not decompose sufficiently, and the methyl groups in TMA were incorporated into SiC.
[0078] Figure 21 is a graph showing the results of X-ray diffraction measurement of Al-doped SiC. As shown in Figure 21, when the needle valve opening length was 0.50 mm, an Al4C3 peak was observed. On the other hand, when the opening length was 0.25 mm or less, no Al4C3 peak was observed. As a result, it was found that when the flow rate of TMA was high, Al4C3 crystallized. The results of Figures 20 and 21 showed that it was necessary to suppress the flow rate of TMA.
[0079] Further, elemental analysis was performed by XPS on the formed Al-doped SiC. Figures 22 to 25 are graphs showing the results of XPS measurement, with Figure 22 showing Si2p, Figure 23 showing C1s, Figure 24 showing O1s, and Figure 25 showing Al2p.
[0080] As shown in Figures 22 to 24, there was no significant change in the Si2p, C1s, and O1s peaks even when the TMA flow rate was changed. On the other hand, as shown in Figure 25, the Al2p peak intensity increased as the TMA flow rate increased. As a result, it was found that the Al doping amount can be controlled by the TMA flow rate.
[0081] Next, the composition ratio of Al-doped SiC was calculated from the XPS measurement results. Figure 26 is a graph showing the composition ratio of Al-doped SiC. It was found that the amount of Al doped also increased by increasing the flow rate of TMA by increasing the opening length of the needle valve. It was also found that the ratio of Si to C became smaller than 1 as the Al composition ratio increased. This is thought to be the effect of methyl groups in TMA being introduced into SiC.
[0082] Next, the resistivity of Al-doped SiC was measured by four-probe measurement. Figure 27 is a graph showing the relationship between the resistivity of Al-doped SiC and the Al composition. As shown in Figure 27, it was found that the resistivity drops significantly when the Al composition is 2% or less.
[0083] Figure 28 is a graph showing the measurement results of the Hall effect for Al-doped SiC. The Al composition was set to 1%. From Figure 28, the Hall concentration was 4.7 × 10 17 cm -3 From this, it was found that the hole concentration can be increased by 1×10 18 cm -3 It is believed that control is possible within the following range. [Explanation of symbols]
[0084] 10: Reaction chamber 11: Stage 12: Heater 13: Supply pipe 14: Exhaust pipe
Claims
1. A method for producing SiC by forming SiC on a substrate by a thermal CVD method using vinylsilane as a raw material, comprising the steps of: the substrate has a metal layer as a top layer, the metal layer being a metal containing any one of Fe, Co, and Ni as a main component; A method for producing SiC, comprising the steps of: forming SiC at a growth temperature of 1000° C. or less.
2. The method for producing SiC according to claim 1 , wherein the thickness of the metal layer is 200 nm or less.
3. 3. The method for producing SiC according to claim 2, wherein a growth temperature is set to be higher than 900° C. and lower than 1000° C., thereby reacting the metal layer with Si of vinylsilane to form a hemispherical silicide, and forming SiC on the surface of the silicide after the metal layer disappears, thereby forming hemispherical SiC.
4. 3. The method for producing SiC according to claim 2, wherein the SiC is formed into granular form by setting the growth temperature at 800° C. or less.
5. The method for producing SiC according to claim 2 , wherein the growth temperature is set to be higher than 800° C. and equal to or lower than 900° C., thereby forming the SiC into a pillar shape.
6. 2. The method for producing SiC according to claim 1, wherein the thickness of the metal layer is made thicker than 200 nm, the growth temperature is made higher than 900° C., carbon fibers are formed on the metal layer, and then the growth temperature is made 900° C. or lower to form SiC coating the carbon fibers.
7. The method for producing SiC according to claim 1 , wherein the metal layer is made thicker than 200 nm and the growth temperature is set to 900° C. or less, thereby forming the SiC into granular form.
8. The method for producing SiC according to any one of claims 1 to 7, wherein Al-doped p-type SiC is formed by supplying a mixture of vinylsilane and trimethylaluminum.
9. The method for producing SiC according to claim 8 , wherein the Al-doped p-type SiC has a ratio of Al to SiC of 1 at % or less.
10. The method for producing SiC according to claim 1 , wherein a flow rate of vinylsilane is equal to or greater than 1 sccm and equal to or less than 50 sccm.
11. The method for producing SiC according to claim 1 , wherein a growth pressure is 100 Pa or less.
12. A fiber material comprising: a carbon fiber having a diameter of 5 nm or more and 100 nm or less and a length of 100 nm or more and 10 μm or less; and SiC coating the carbon fiber.